Penggunaan Biofilter untuk Menghilangkan Bau pada Sludge Industri Es Krim: Utilization of Biofilters to Remove Odors in Ice Cream Industry Sludge - Abdul Aziz Setiawan; Sri Sugiarti; Hanies Ambarsari (Jurnal Teknologi Lingkungan, 2022)
The growing number of industries in Indonesia causes industrial waste to increase. Substances with upleasant smell from industrial waste can pollute the environment. Currently, not many people process and utilize industrial waste in the form of sludge left over from the WWTP process. The biofilter method will be very effective in handling air pollution because it has several advantages, among them are an easy and simple process, low investment and operational costs, and a relatively long operational time. The study began with the manufacture of incubation equipment and biofilter columns, testing the feasibility of the biofilter and incubation column, selecting fillers based on the results of a literature review, sampling fillers, preparing fillers, preparing samples of ice cream waste sludge from the ice cream industry in the Jababeka area, followed by analysis proximate sludge, analysis of ammonia gas in sludge with various variations of sludge weight and time, biofiltration process using coconut shell charcoal in order to obtain optimal variations in coconut shell charcoal size, then biofiltration using coconut shell charcoal briquettes with added zeolite content variations to determine the most effective filler material to remove odors. The results show that coconut shell charcoal with a particle size of 100 mesh is the most optimal biofilter filler for removing ammonia gas with an efficiency of 75% compared to a particle size of 20 mesh and 60 mesh which has an ammonia gas removal efficiency of 64% and 68%. Biofilter IV has the highest efficiency in removing ammonia gas, which is 90%. Keywords: Black soldier fly maggot, Biofilter, Coconut shell charcoal. Zeolite, Odor remover ABSTRAK Semakin banyaknya industri di Indonesia menyebabkan limbah industri semakin meningkat. Zat yang berbau dari limbah hasil industri dapat mencemari lingkungan. Saat ini belum banyak yang mengolah dan memanfaatkan limbah industri berupa sludge sisa proses IPAL. Metode biofilter akan sangat efektif dalam penanganan pencemaran udara karena memiliki beberapa keuntungan, diantaranya proses yang mudah dan sederhana, biaya investasi dan operasional yang rendah, serta waktu operasional yang relatif dapat bertahan lama. Penelitian diawali dengan pembuatan alat inkubasi dan kolom biofilter, pengujian kelaikan kolom biofilter dan inkubasi, pemilihan bahan pengisi berdasarkan hasil kajian literatur, sampling bahan pengisi, preparasi bahan pengisi, preparasi sampel sludge limbah es krim  dari  industri es krim di wilayah Jababeka, dilanjutkan dengan analisis proksimat sludge, analisis gas amonia pada sludge dengan berbagai variasi bobot sludge dan waktu, proses biofiltrasi menggunakan arang tempurung kelapa agar didapatkan variasi ukuran arang tempurung kelapa yang optimal, kemudian biofiltrasi menggunakan briket arang tempurung kelapa yang ditambahkan variasi kandungan zeolit untuk mengetahui bahan pengisi yang paling efektif menghilangkan bau. Hasil penelitian didapatkan bahwa arang tempurung kelapa dengan ukuran partikel 100 mesh adalah bahan pengisi biofilter yang paling optimal untuk menghilangkan gas amonia dengan efisiensi sebesar 75% dibandingkan dengan ukuran partikel 20 mesh dan 60 mesh yang memiliki nilai efisiensi penghilangan gas amonia sebesar 64% dan 68%. Biofilter IV memiliki nilai efisiensi paling tinggi dalam menghilangkan gas amonia yaitu sebesar 90%. Kata kunci: Black soldier fly maggot, Biofilter, Arang tempurung kelapa, Zeolit, Penghilang bau